IP3 Receptors, Mitochondria, and Ca2+ Signaling: Implications for Aging - Jean-Paul Decuypere; Giovanni Monaco; Ludwig Missiaen; Humbert De Smedt; Jan B. Parys; Geert Bultynck (Journal of Aging Research)
The tight interplay between endoplasmic-reticulum-(ER-) and mitochondria-mediated Ca2+ signaling is a key determinant of cellular health and cellular fate through the control of apoptosis and autophagy. Proteins that prevent or promote apoptosis and autophagy can affect intracellular Ca2+ dynamics and homeostasis through binding and modulation of the intracellular Ca2+-release and Ca2+-uptake mechanisms. During aging, oxidative stress becomes an additional factor that affects ER and mitochondrial function and thus their role in Ca2+ signaling. Importantly, mitochondrial dysfunction and sustained mitochondrial damage are likely to underlie part of the aging process. In this paper, we will discuss the different mechanisms that control intracellular Ca2+ signaling with respect to apoptosis and autophagy and review how these processes are affected during aging through accumulation of reactive oxygen species.